Failure analysis of corroded RC beams subjected to shear-flexural actions. (November 2018) - Recupero, Antonino; Spinella, Nino; Tondolo, Francesco
Abstract: In this paper, the shear-flexural behaviour of corroded reinforced concrete beams is investigated and analytically reproduced. A theoretical model, based on the limit equilibrium theory and able to take into account the shear-flexural interaction, was extended to the case of corroded beams. The effects of compressive concrete strength degradation, due to the volume expansion effect of rust, and of the uniform and localized corrosion are included in the model. In order, to analytically reproduce the decay of the mechanical properties of corrosion-damaged steel rebar, a large database of experimental tensile test on corroded rebars available in literature was collected and a simple equation was proposed. Some experimental tests on corroded reinforced concrete beams, available in literature, where collected and used to validate the proposed model. Moreover, the model was appropriately upgraded to provide the ultimate curvature of the beam, there by the influence of corrosion on the ductility was highlighted. Highlights: Experimental versus theoretical prediction of steel rebar mechanical degradation due to corrosion Experimental versus theoretical prediction of shear-flexural domain of corroded RC beams Analytical prediction of the corrosion influence on the ultimate curvature and ductility